Landscape concept of Pál Teleki and its renaissancein the 21th century - Konkoly-Gyuró, Éva (4D Journal of Landscape Architecture and Garden Art, 2021)
Pál Teleki, a great Hungarian thinker and geo-politician, died 80 years ago. In the heart of his philosophy stood the landscape. He conceived landscape as a human environment, an organic life unit created by man-nature interaction. This view was the foundation of his economic and political geography between the two World Wars. Teleki recognised the unique character of the landscapes formed by people living in them and considered this individuality as a resource. He declared already in 1917: "the basic task of the geography crystallises around the special character of the landscape." During the second half of the 20th century, though, this complex approach wasn't accepted, either in politics or in science. Geography was split into physical and social geography, and landscape studies were subordinated in many countries to physical geography. Areas delineated by administrative, political boundaries – municipalities, counties, regions – became the reference units of the research that took human activities into account. Nature, economy and society were the objects of different studies. The claim for a reunification emerged in the 1960ies by professor Mihály Mőcsényi, the founder of the Hungarian landscape architecture school. He recognised that the environmental problem's cause is the separation of nature and society, urban and rural, and the solution could be their integration within the landscape. Furthermore, in Great Britain, the significance of landscape character in heritage protection and rural development was discovered in the 1980ies. The evolving landscape ateliers served as conceptual background for the European Landscape Convention that opened the floor for an integrative landscape approach and the landscape character concept. Consequently, the renaissance of Teleki's landscape concept started to emerge both in science and planning.
Keywords: Teleki Pál; landscape definition; landscape character; landscape geography; landscape architecture; Council of Europe; Landscape Convention